2015
DOI: 10.1159/000370071
|View full text |Cite
|
Sign up to set email alerts
|

Murine Gammaherpesvirus (MHV-68) Transforms Cultured Cells in vitro

Abstract: Human dermal fibroblasts and mouse NIH/3T3 cells acquired the transformed phenotype (‘criss-cross' pattern of growth) after infection with ultraviolet-irradiated murine gammaherpesvirus (MuHV-4 strain 68; MHV-68). These cells with changed phenotype could be serially cultured for 5-6 passages (35-40 days), and then they entered into crisis and most of them died. In a small number of cultures, however, foci of newly transformed cells appeared from which two stable cell lines were derived. After 6-9 cell culture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
11
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 16 publications
(14 reference statements)
5
11
0
1
Order By: Relevance
“…However, it was demonstrated in some cases that NR was not effective in the treatment of herpetic lesions [14][15][16] . In our previous study, we demonstrated that UV-inactivated MHV-68 can transform cells in vitro [27] , thus resembling the transforming ability of several UV-inactivated herpesviruses belonging to the subfamily Alphaherpesvirinae, such as HSV1, HSV2, and EHV [24][25][26]39] . Recent studies have reported that normal cell lines such as MRC-5 and NIH-3T3 (used in this study) cultured in the presence of MB acquired a transformed phenotype accompanied by the presence of virus when they were infected with photoinactivated nonsyn strains (K17 and Kupka) but not syn strains (HSZP) of HSV-1 [40] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it was demonstrated in some cases that NR was not effective in the treatment of herpetic lesions [14][15][16] . In our previous study, we demonstrated that UV-inactivated MHV-68 can transform cells in vitro [27] , thus resembling the transforming ability of several UV-inactivated herpesviruses belonging to the subfamily Alphaherpesvirinae, such as HSV1, HSV2, and EHV [24][25][26]39] . Recent studies have reported that normal cell lines such as MRC-5 and NIH-3T3 (used in this study) cultured in the presence of MB acquired a transformed phenotype accompanied by the presence of virus when they were infected with photoinactivated nonsyn strains (K17 and Kupka) but not syn strains (HSZP) of HSV-1 [40] .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, transformation of MRC-5 and NIH-3T3 cells in vitro was demonstrated after infection with UV-irradiated alpha-herpesviruses, HSV-1 and HSV-2 [24][25][26] . Moreover, UV-irradiated murine gamma-herpesvirus 68 (MHV-68) enabled the transformation of human and mouse dermal fibroblast cells in which the disappearance of actin bundles was demonstrated [27] .…”
Section: Introductionmentioning
confidence: 99%
“…PRGF and HSGF-2 exhibit transformation activity in vitro [2,8,9,10,11]. Recently, similar activities of murine gammaherpesvirus (MHV-68) were described [12,13]. …”
Section: Figmentioning
confidence: 99%
“…The oncogenic potential of some alpha- or betaherpesviruses has been studied for over 2 decades. The transforming activity of MHV-68 was demonstrated on the tumor cell line S11 derived from MHV-68 infected mice growing into tumors in nude mice, human dermal fibroblasts, and mouse NIH/3T3 cells infected with ultraviolet-irradiated MHV-68 [12,31]. Further studies will be required to determine differences in the composition of MHGFA and MHGFW and the possible role of gB, US3, UL24, and other viral and cellular proteins in cell transformation and oncogenesis.…”
Section: Figmentioning
confidence: 99%
“…V bunkách transformovaných s MHV-68 bola dokázaná víru-sová DNA metódou PCR a vírusový antigén pomocou imunofluorescencie. Imunofluorescenčné štúdie však navyše ukázali, že v transformovaných bunkách dochádza k rozpadu aktínových filamentov [52]. Podobne bola možná transformácia po infekcii fotoinaktivovaným vírusom, t. j. ak bol vírus zafarbený neutrálnou červeňou alebo metylénovou modrou a ožiarený viditeľným svetlom [53][54][55].…”
Section: Mechanizmus "Hit and Run"unclassified